2015
DOI: 10.1111/jcpt.12343
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the number of daily pills and doses on adherence to antiretroviral treatment: a 7-year study

Abstract: There has been a continuous reduction in the number of pills and doses of antiretrovirals taken by individual patients over the last 7 years due largely to the introduction of improved treatments and regimens. More daily pills or doses was not associated with worse ART adherence in our pharmaceutical care programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“… Determine the risk of therapy interruption of STR compared to BID or OD EFV therapy. Arroyo et al 2016 19 Spain Retrospective study 264 patients on ART treatment Evaluate the influence of the number of daily pills and daily doses on treatment adherence in a 7-year pharmaceutical care program. Velvanathan et al 2016 20 Malaysia Randomized control trial.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… Determine the risk of therapy interruption of STR compared to BID or OD EFV therapy. Arroyo et al 2016 19 Spain Retrospective study 264 patients on ART treatment Evaluate the influence of the number of daily pills and daily doses on treatment adherence in a 7-year pharmaceutical care program. Velvanathan et al 2016 20 Malaysia Randomized control trial.…”
Section: Resultsmentioning
confidence: 99%
“… 6 , 15 , 18 , 20–22 One study did not assess the clinical outcomes associated with regimen simplification. 19 On the other hand, eight studies were identified that reported on the simplification of drug regimens related to other medical conditions. These included three that were conducted in the US, 13 , 14 , 24 two in Germany, 7 , 10 and one each in Hungary, Australia and South Korea.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Group, 2015) and INSIGHT START (Insight Start Study Group et al, 2015) studies. Further, modern regimens have fewer adverse effects (Margolis, Heverling, Pham, & Stolbach, 2014) and decreased pill burden and dosing frequency (Hernandez Arroyo et al, 2016). Globally consensus has been reached; since 2015 guidelines uniformly recommend immediate initiation of ART regardless of CD4 cell count (Lundgren, Gatell, Rockstroh, & Furrer, 2015;Thompson et al, 2012;WHO, 2015).…”
Section: Introductionmentioning
confidence: 99%